The impact of livestock interventions on nutritional outcomes of children younger than 5 years old and women in Africa: a systematic review and meta-analysis - Muema, Josphat; Mutono, Nyamai; Kisaka, Stevens; Ogoti, Brian; Oyugi, Julius; Bukania, Zipporah; Daniel, Tewoldeberhan; Njuguna, Joseph; Kimani, Irene; Makori, Anita; Omulo, Sylvia; Boyd, Erin; et al. (Frontiers in Nutrition, 2023)
Background: Nutrition-sensitive livestock interventions have the potential to improve nutrition of communities dependent on livestock for their livelihoods by increasing availability and access to animal source foods, or incomes improving their purchasing power for other foods and determinants of health. However, there is a dearth of synthesized empirical evidence on the impact and effect of livestock interventions on diets and human nutritional status in Africa. Objective: To review evidence of the effectiveness of nutrition-sensitive livestock interventions in improving diets and nutrition status among children <5 years of age as well as pregnant and lactating women. Methods: Following PRISMA guidelines, we conducted a systematic review and meta-analysis of published studies reporting on effect of livestock interventions on maternal and child nutrition in Africa. Data was extracted, synthesized, and summarized qualitatively. Key outcomes were presented in summary tables alongside a narrative summary. Estimation of pooled effects was undertaken for experimental studies with nutritional outcomes of consumption of animal source foods (ASFs) and minimum dietary diversity (MDD). Fixed effects regression models and pooled effect sizes were computed and reported as Odds Ratios (ORs) together with their 95% confidence intervals (CI). Results: After screening, 29 papers were included in the review, and of these, only 4 were included in the meta-analysis. We found that nutrition-sensitive livestock interventions have a significant positive impact on consumption of ASFs for children <5 years (OR = 5.39; 95% CI: 4.43 – 6.56) and on the likelihood of meeting minimum dietary diversity (OR = 1.89; 95% CI: 1.51 – 2.37). Additionally, the impact of livestock interventions on stunting, wasting and underweight varied depending on type of intervention and duration of the program/intervention implementation. Therefore, because of this heterogeneity in reporting metrics, the pooled estimates could not be computed. Conclusion: Nutrition-sensitive livestock interventions showed a positive effect in increasing consumption of ASFs leading to improved dietary diversity. However, the quality of the evidence is low and therefore, more randomized controlled studies with consistent and similar reporting metrics are needed to increase the evidence base on how nutrition–sensitive livestock interventions affect child growth outcomes.